SOFTWARE PRODUCTS FOR CREATING EDUCATIONAL VIDEO COURSES FOR PEOPLE WITH PHYSICAL DISABILITIES - Denisova, Diana; Levanova, Natalia; Tolmachev, Oleg; Dobrova, Ekaterina (Revista Inclusiones, 2020)
The article identifies the benefits of implementing information and communication technologies in inclusive education, areas, in which information and communication technology support are recommended, as well as the main types of information and communication technologies suitable for use as a support tool for inclusive learning. The authors characterize the main problems of implementing information and communication technologies to support inclusive education and the conditions, the implementation of which will help to prevent them.